2009
DOI: 10.1109/tns.2009.2026475
|View full text |Cite
|
Sign up to set email alerts
|

Basic Properties of Ceramic Pr:LuAG Scintillators

Abstract: This paper describes the first report of a Pr 3+ -doped transparent ceramic Lu3Al5O12(Pr:LuAG) scintillator. Transparent ceramic Pr 0.25 mol% doped LuAG was developed by a sintering method, and achieved 70% transparency at wavelengths longer than 310 nm. The emission wavelength of the ceramic Pr:LuAG shifts to longer wavelengths than that of its single crystalline counterpart. The light yield was measured by irradiation of 137 Cs, and was almost half as that of the single crystalline counterpart. The energy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Similar to the materials listed above, the Nd-doped Lu 3 [11], and recently, some other groups demonstrated their progress on research of these materials [12,13]. These following communications reported not scintillation but photo-luminescence performance of these ceramics which sometimes differs from scintillation responses.…”
mentioning
confidence: 74%
“…Similar to the materials listed above, the Nd-doped Lu 3 [11], and recently, some other groups demonstrated their progress on research of these materials [12,13]. These following communications reported not scintillation but photo-luminescence performance of these ceramics which sometimes differs from scintillation responses.…”
mentioning
confidence: 74%
“…The similar absorption band can be also seen in Lu 2 Si 2 O 7 :Pr 3+ [20] and LuAG:Pr 3+ crystals [21], which belongs to the 4f 2 → 4f 1 5d transitions of Pr 3+ . The dispersion of the on-set of the cut-off edge locates at 250 nm, which has obviously blue-shift comparing to the value of LuAG:Pr 3+ crystal round 300 nm [22] and similar with the value of Lu 2 Si 2 O 7 :Pr 3+ [23]. Although the maximum optical transmittance of Lu 0.8 Sc 0.2 BO 3 :1 at%Pr 3+ crystals with 1 mm and 3 mm thickness both can reach ∼76%, there is an significant absorption valley locating in the region from 250 to 600 nm.…”
Section: Optical Characteristicsmentioning
confidence: 87%
“…This advantage makes the praseodymium-doped scintillators have always been the concern of researchers until now [20][21][22]. However, to our knowledge, there is no report about the luminescence characteristics of praseodymium doped lutetium scandium orthoborate crystal.…”
Section: Introductionmentioning
confidence: 99%
“…% Pr:LuAG ceramics. 18, the latter demonstrated an energy resolution of 12% at 662 keV irradiated by 137 Cs in Pr:LuAG ceramics of 0.25 mol %. 8͒.…”
Section: Scintillation Propertiesmentioning
confidence: 94%
“…10,11 More recently, also fast emitting Ce 3+ centers were employed in YAG and LuAG scintillation ceramics 12,13 and scintillation decays ͑SDs͒ dominated by several tens of ns decay times were demon-strated. Yanagida et al 18 has recently reported fabrication of 0.25 mol % Pr:LuAG ceramics, the transmission of which reaches 70% beyond 310 nm. 13 Growth of Pr-doped LuAG SCs has been reported by either Czochralski or micropulling-down ͑PD͒ method.…”
Section: Microstructure Optical and Scintillation Characteristics Omentioning
confidence: 99%